NETRALITAS KEPALA DESA TANJUNG DALAM MENGAWAL PEMILIHAN UMUM 2024 MENURUT UNDANG-UNDANG NO 7 TAHUN 2017 TENTANG PEMILIHAN UMUM: NETRALITAS KEPALA DESA TANJUNG DALAM MENGAWAL PEMILIHAN UMUM 2024 MENURUT UNDANG-UNDANG NO 7 TAHUN 2017 TENTANG PEMILIHAN UMUM - admin, Admin; Fitrotun Nisak; Muhammad Zainal; Fathul Qorib (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract Election is a means of people's sovereignty to elect members of the DPR, DPD, DPRD, President and vice President. Law Number 7 of 2017 regulates various aspects of the implementation of elections in Indonesia, including the neutrality of village heads in carrying out their duties and responsibilities during the Election process. The village head has an important role as an election organizer at the village or village level. This research aims to ensure that the head of Tanjung village can carry out his role neutrally and free from interventions and intimidation that affect the course of the 2024 election. This research is an empirical research, the location of the research was carried out in Tanjung Pajarakan village with the method of Interview, Observation, Document Analysis, Literature Study and Technical Data Analysis The results of the research show that the head of Tanjung village has a strategic role in overseeing the 2024 election process at the village level but the head of Tanjung village is also faced with various challenges, such as pressure and intervention from parties who want to influence the election process at the village level Keywords:Neutrality, Village chief, General election